American Sniper : the Autobiography of the Most Lethal Sniper in U.S. Military History - Kyle, Chris 1974-2013.; DeFelice, Jim 1956-; McEwen, Scott (New York : William Morrow, 2013)
A commemorative memorial edition of Kyle's 2012 autobiography which includes more than 80 pages of remembrances by those whose lives he touched, including family members, fellow Navy SEALS, veterans and wounded warriors, and friends.
Evil in the crosshairs -- Bustin' broncs and other ways of having fun -- Jackhammered -- Takedowns -- Five minutes to live -- Sniper -- Dealing death -- Down in the shit -- Family conflicts -- The punishers -- The devil of Ramadi -- Man down -- Hard times -- Mortality -- Home and out.
Keywords: Kyle, Chris, -- 1974-2013; United States -- Navy -- Biography; Iraq War, 2003- -- Personal narratives, American; Snipers -- Biography -- United States